Consumption-based carbon emissions, renewable energy consumption, financial development and economic growth in Chile - Kirikkaleli, Dervis; Gungor, Hasan; Adebayo, Tomiwa Sunday (Wiley, 2022)
This paper aims to investigate the effect of financial development and renewable energy consumption on consumption-based CO2 emissions in Chile while controlling for economic growth and electricity consumption. Based on the aim of the paper, autoregressive distributed lag (ARDL) bounds with Kripfganz and Schneider's (2018) approximations, fully modified ordinary least square (FMOLS), dynamic ordinary least square (DOLS), and gradual shift causality tests are applied in this study. The outcomes clearly reveal that while financial development and renewable energy consumption reduce the consumption-based CO2 emissions in Chile, economic growth and electricity consumption increase consumption-based carbon emissions. The gradual shift causality test provides consistent results with ARDL, FMOLS, and DOLS estimators. Therefore, policymakers in Chile should dynamically encourage the research and development of low-carbon technologies and renewable energy investments while imported nonrenewable energy sources level should be targeted, and especially those sectors which are more energy-intensive and causing to increase in consumption-based CO2 emissions.
Keywords: Chile; consumption-based CO2 emissions; economic growth; financial development; renewable energy consumption